Reference values and prediction of sarcopenia in Japanese men and women - Kiyoshi Sanada; Motohiko Miyachi (Japanese Society of Physical Fitness and Sports Medicine, 2012)
In this article, we determine the reference values for sarcopenia, and test the hypothesis that sarcopenia is associated with risk factors for cardiovascular disease. Moreover, we develop prediction models of sarcopenia in Japanese men and women. A total of 1,488 Japanese men and women, aged 18-85 years, participated in this study. Appendicular muscle mass (AMM) was measured by dual-energy X-ray absorptiometry. Reference values for classes 1 and 2 sarcopenia (skeletal muscle index; AMM/height2, kg･m-2) in each sex were defined as values one and two standard deviations below the sex-specific means of reference values obtained in this study from young adults aged 18-40 years. The reference values for classes 1 and 2 sarcopenia were 7.77 kg･m-2 and 6.87 kg･m-2 in men, and 6.12 kg･m-2 and 5.46 kg･m-2 in women, respectively. In subjects with both class 1 and class 2 sarcopenia, body mass index and % body fat were significantly lower than in normal subjects. Despite this, whole blood glycohaemoglobin A1c in men with class 1 sarcopenia was significantly higher than in normal subjects, and brachial-ankle pulse wave velocity in women, with both class 1 and class 2 sarcopenia, was significantly higher than in normal subjects. Stepwise regression analysis indicated that the body mass index (BMI), waist circumference, and age were independently associated with skeletal mass index (SMI) in men; and BMI, handgrip strength, and waist circumference were independently associated with SMI in women. The SMI prediction equations were applied to the validation group, and strong correlations were also observed between DXA (dual-energy x-ray absorptiometry) -measured and predicted SMI in men and women. We concluded that sarcopenia is associated with more glycation of serum proteins in men and with greater arterial stiffness in women. Moreover, the prediction models of SMI using anthropometric measurement are valid for alternative DXA-measured SMI in Japanese adults.